Probabilistic longevity estimate for the LUSI mud volcano, East Java - Davies, R.; Mathias, S.; Swarbrick, R.; Tingay, Mark (Geological Society Publishing House, 2011)
A new method for estimating the duration of a mud volcano eruption is applied to the LUSI mud volcano in East Java. The estimate is based upon carbonates at depths in the range 2500-3500 m being the water source, with an estimated area of 100-600 km2, thickness of 0.2-1.0 km, porosity of 0.15-0.25, an initial pressure between 13.9 and 17.6 MPa, and a separate, shallower source of mud (c. 1200-1800 m depth). The resulting 50 percentile for the time it takes for flow to decline to <0.1 Ml day-1 is 26 years. By analogy with natural mud volcanoes it can be expected to continue to flow at lower rates for thousands of years. Assuming subsidence rates of between 1 and 5 cm day-1, land surface subsidence of between c. 95 and c. 475 m can be expected to develop within the 26 year time period.